Dialogue between literature and psychoanalysis - Trzaskowski, Zbigniew (Wydawnictwo Uniwersytetu Jana Kochanowskiego w Kielcach, 2025)
The lasting influence of Sigmund Freud’s work on many fields of science and social thought has also left its mark on literature. Psychoanalysis has become a rich source of motifs, including the metaphysics of the will, unconsciousspiritual life, pathological manifestations of love, and the semantics of dreams. The archetypal contexts of meaning and the original associative method of psychoanalytic treatment led to the crystallisation of new literary strategies and forms of writing (internal monologue, stream of consciousness, the equivalencing of emotional states).